Technology innovation and carbon efficiency in Africa: what is the role of digitalization and digital inclusive finance? - Amowine, Nelson; Li, Huaizong; Baležentis, Tomas; Štreimikienė, Dalia (Technological and Economic Development of Economy, 2025)
Improving carbon efficiency and mitigating carbon emissions is fundamental to sustainable development and the well-being of human society. Yet, no study highlighted and identified the drivers of carbon efficiency in Africa. Specifically, an empirical study on the role of technological innovation (GTI), digitalization, and digital inclusive finance (DIF) in improving carbon efficiency (CEE) in Africa is rare. To fill this gap, this study investigates the synergistic impact of green technological innovation (GTI), digitalization, and digital inclusive finance (DIF) on improving carbon efficiency (CEE) from the African perspective. A meta-frontier slack-based environmental polluting technology and mixed integervalued data envelopment analysis (DEA) is framed to gauge the carbon efficiency across oil-endowment and non-oil-endowment African countries from 2010 to 2019. The results indicate that only a few African countries appeared to be operating at efficient production levels. The bootstrapped regression results indicated an invented U-shaped nexus is established between carbon efficiency and African economic development via the extended stochastic impacts by regression on population, affluence, and technology (STIRPAT) framework. Internet usage and mobile cellular subscriptions as components of digitalization positively improve Africa’s carbon efficiency. Mobile money transaction innovation (i.e., active mobile money agents per 1000 km2) as a dimension of digital inclusive finance conserves Africa’s environmental efficiency. Green technological innovations did not drive carbon efficiency significantly in Africa and the two groups. Based on the empirical findings, pragmatic policy strategies are further discussed to boost carbon efficiency and mitigate environmental degradation in Africa.